Study Direction to Oxidize a Local Pine Rosin with Potassium Permanganate - Widia Edy Kuncoro; Masruri MASRURI, Ph.D; Siti Mariyah Ulfa; Moh. Farid Rahman (Chemistry Department, The University of Brawijaya, 2023)
Pine rosin acid or Gondorukem is a solid resin obtained from pine sap. It is yielded as residue from a high temperature distillation process. In industry, rosin acid is widely used and modified as raw material in paint, ink, adhesive, resin, thermoplastic, and thermosetting polymer. Modification process generally is undergone to generate rosin acid with specific properties and for certain purposes. This paper report, potassium permanganate oxidation reaction of pine rosin acid under acidic process at low temperature. Product identified as 13,14-seco-13-oxoabiet-7-ene-dioic acid (0.52%), 7,8-dihydroxy-abietic acid (6.62%), and 7-oxo-dehydroabietic acid (1.49%). The crude product was isolated as a pale to white solid. Under high temperature a yellowish product was resulted. In overall, the yield isolated in between 46.4% and 86.0%.